PENGARUH RASIO DAN KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA INDEKS LQ45 DI BURSA EFEK INDONESIA (BEI) PERIODE 2015-2016 - I Nyoman Sutapa (Faculty of Economics and Business, Universitas Warmadewa, 2018)
This study aims to test whether the ratio analysis consisting of Current Ratio (CR), Debt Equity Ratio (DER), Return on Equity (ROE), and Financial Performance consisting of Earning per share (EPS) have an effect on Stock Price. The population in this study is the company that entered in the index LQ45 in 2015-2016. The sampling technique used in this study is by purposive sampling where the sample is selected on the basis of certain considerations or criteria and the number of samples obtained in the study were 56 companies. The results showed that: (1) Current Ratio has a positive effect on stock prices. (2) .Debt to Equity Ratio does not affect the stock price. (3) .Return on Equity does not affect the stock price (4) .Earning per share has a positive effect on stock prices. Keywords : Current Ratio, Debt Equity Ratio, Return on Equity, Earning per share, Stock Price.